ONE-DIMENSIONAL TRANSPORT AND GATING OF INAS/GASB STRUCTURES - Chen, Y; Symons, D; Lakrimi, M; Salesse, A; Houston, G; Nicholas, R; Mason, N; Walker, P (Academic Press Ltd, 1994)
Semimetallic InAs/GaSb structures are known to contain simultaneously both two dimensional electrons in the InAs and two dimensional holes in the GaSb layers. Following successful anodisation of undoped GaSb, we describe transport measurements performed on a wide area gated sample and also a single quantum point contact. In the large area gated sample, the electron density increases and the hole density decreases when a positive gate voltage is applied. Under negative bias, an additional layer of holes is created at the interface between the insulating and GaSb capping layers, which is confirmed by self-consistent modelling of the band profile under external bias. The conductance of the point contact is found to exhibit quantised values.